Biochars improve aggregate stability, water retention, and pore‐space properties of clayey soil. Issue 1 (8th October 2013) - Sun, Fangfang; Lu, Shenggao
Abstract The influence of biochar amendments on the physical quality of a clayey soil (Vertisol) was evaluated by aggregate‐size distribution and stability, water retention, and pore‐space structure of biochar‐amended soils. Clayey soil was treated with three kinds of biochars (straw biochar, woodchips biochar, and wastewater‐sludge biochar) at the rate of 0, 20, 40, and 60 g biochar (kg soil)–1 and incubated for 180 d in glasshouse. The application of straw biochar (SB) and wastewater‐sludge biochar (WSB) significantly enhanced the formation of 5–2 and 0.25–0.5 mm macroaggregates in the clayey soil relative to the control treatment, while the < 0.25‐cm microaggregate decreased with biochar additions. However, woodchips biochar (WCB) had no obvious effect on the formation of macroaggregate. The application of SB and WSB increased the mean weight diameter (MWD) and geometric mean diameter (GMD) of clayey soil, implying that biochar increased the aggregate stability. They improved the aggregate stability through an enhanced resistance to slaking and increased interparticular cohesion. The SB‐amended soils exhibited significant increases in the available water contents of soils. The application of SB significantly increased pore volume in the macropore (> 75 μm) and mesopore (30–75 μm) ranges, which may be the result of the reorganization of pore‐size distribution and aggregation processes induced by the addition of biochar. Results indicated that biochar had the potential to improve the physical quality and pore‐space status of clayey soil. It is suggested that biochar may be considered as a soil amendment for improving poor physical characteristics of clayey soil.